RESEARCH OF INFLUENCE OF THE HIGH-SPEED THERMAL PROCESSING REGIMES ON STRUCTURE AND MECHANICAL PROPERTIES OF PIPE STEEL 32G2 - A. I. Gordienko; O. M. Kirilenko; I. I. Vegera; D. A. Semenov (Литьë и металлургия)
Researches on influence of high-speed heating temperature, regimes of cooling and temperature of abatement on structure and mechanical properties of pipe steel 32G2 are carried out. Recommendations on the regimes of high-speed thermal processing of steel 32G2 which can be used at manufacturing of seamless pipes are given.